The Role of TAMs in Tumor Microenvironment and New Research Progress - Yawei Feng; Zhiqiang Ye; Furong Song; Yufeng He; Jun Liu (Stem Cells International)
Tumor-associated macrophages (TAMs) are an important part of tumor microenvironment (TME) and play a key role in TME, participating in the process of tumor occurrence, growth, invasion, and metastasis. Among them, metastasis to tumor tissue is the key step of malignant development of tumor. In this paper, the latest progress in the role of TAMs in the formation of tumor microenvironment is summarized. It is particularly noteworthy that cell and animal experiments show that TAMs can provide a favorable microenvironment for the occurrence and development of tumors. At the same time, clinical pathological experiments show that the accumulation of TAMs in tumor is related to poor clinical efficacy. Finally, this paper discusses the feasibility of TAMs-targeted therapy as a new indirect cancer therapy. This paper provides a theoretical basis for finding a potentially effective macrophage-targeted tumor therapy.